Neologisms in Modern Russian: Linguistic Analysis and Development Trends (Based on Uzbekistan) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article examines the features of the formation and functioning of neologisms in modern Russian. The reasons for their emergence, sources of borrowing, and main semantic types are analyzed. Particular attention is paid to the influence of the digital environment on lexical innovation. The study is based on materials from media, social networks, and online communication. Conclusions are drawn regarding the active expansion of the Russian lexicon due to technological and socio-cultural factors.